Fundamentals of nursing : human health and function - Craven, Ruth F.; Hirnle, Constance J. (Philadelphia, Pa. : Lippincott, 1992)
(NtOW^ HURAANGUJs
Includes bibliographical references and index.
Keywords: Nursing; Health Promotion -- nurses' instruction; Nursing Process